Determinants of Entrepreneurial Intention in Gender Perspective: Evidence from Indonesia - Sunanto Sunanto; Hamdy Hady; Horas V Purba (International Journal of Islamic Business and Management Review, 2023)
This study aims to investigate entrepreneurial intention and its determinants in a gender perspective of professional pharmacists within the Greater Jakarta of Indonesia by referring to the theory of planned behavior (TPB). Research on entrepreneurial intention and its determinants in the field of ‘pharmapreneurship’ with professional pharmacists as research subjects is still not widely revealed. This research uses a quantitative approach with a cross-sectional survey model. The population of this study is all pharmacists registered with the Indonesian Pharmacists Association (IAI) in the area of the Greater Jakarta of Indonesia. Based on the Slovin formula (error 5%) obtained a sample number of 391 pharmacists, with proportional random sampling. The Independent t-test was conducted to investigate mean differences of the EI and its determinants between male and female of professional pharmacists. The results showed that the mean difference on entrepreneurial intention (EI), entrepreneurial attitude (EA) and entrepreneurial self-efficacy (ESE) between male and female of professional pharmacists are significantly rejected except for entrepreneurial education (EE). The paper provides evidence that equality between gender settings need to be considered in the design and delivery of the determinants except EE if they are to have the desired impact on entrepreneurial intention. The research findings are of interest to business, academia and policy makers.